2022
DOI: 10.1021/acsami.2c03905
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Immunosensor Based on Gold-Graphene Oxide Nanocomposites with Ionic Liquid for Detecting the Breast Cancer CD44 Biomarker

Abstract: We develop a highly sensitive electrochemical immunosensor for the detection of a cluster of differentiation-44 (CD44) antigen, a breast cancer biomarker. The hybrid nanocomposite consists of graphene oxide, ionic liquid, and gold nanoparticles (GO-IL-AuNPs) immobilized on a glassy carbon electrode. GO favors the immobilization of antibodies because of the availability of oxygen functionalities. However, 1-butyl-3-methylimidazolium tetrafluoroborate (BMIM.BF4) and AuNPs facilitate electron transfer and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Graphene oxide (GO) is an oxidized form of graphene that contains numerous oxygen-containing functional groups on its surface because of the powerful effects of certain oxidizing agents, which render GO hydrophilic and biocompatible for a wide range of biomedical applications. Previous studies have demonstrated that GO could adsorb single-stranded DNA through π–π stacking and hydrogen bonding, while dsDNA bases were shielded by negatively charged phosphate groups and had a low affinity for GO. The use of GO in the PCR system can promote the formation of primer–template complexes and accelerate PCR rates. A previous study has reported on the introduction of graphene oxide quantum dots into the qRT-PCR system to improve its performance .…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO) is an oxidized form of graphene that contains numerous oxygen-containing functional groups on its surface because of the powerful effects of certain oxidizing agents, which render GO hydrophilic and biocompatible for a wide range of biomedical applications. Previous studies have demonstrated that GO could adsorb single-stranded DNA through π–π stacking and hydrogen bonding, while dsDNA bases were shielded by negatively charged phosphate groups and had a low affinity for GO. The use of GO in the PCR system can promote the formation of primer–template complexes and accelerate PCR rates. A previous study has reported on the introduction of graphene oxide quantum dots into the qRT-PCR system to improve its performance .…”
Section: Introductionmentioning
confidence: 99%
“…Cancer, malignant tumors, autoimmune deficiency diseases, and degenerative neurological diseases are all threatening human life and health all the time, which raises numerous challenges to the diagnosis and treatment according to the World Health Organization (WHO). , MicroRNA (miRNA), as a short nucleic acid sequence, can control the malignant expression and biological activities of many gene, making it an innovative approach for the preliminary touch and discharge and prognosis recovery of these major diseases. Therefore, the excavation of rapid, efficient, and ultrasensitive detection technology of miRNA can not only precipitate the detection rate of diseases effectively but also retrench the window period of pathogen detection greatly. , At present, the technologies that have been explored incorporate surface-enhanced Raman spectroscopy (SERS), fluorescence (FL), photoelectrochemistry (PEC), chemiluminescence, and electrochemiluminescence (ECL) , and have shown preeminent practical implications. Among them, ECL has captivated increasingly deliberation and brilliance owing to the minimal background noise, ultrahigh sensitivity, extremely low detection limit, and admirable electrochemical performance and has become an indispensable part in the areas of clinical medicine, food security, environmental monitoring, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer, malignant tumors, autoimmune deficiency diseases, and degenerative neurological diseases are all threatening human life and health all the time, which raises numerous challenges to the diagnosis and treatment according to the World Health Organization (WHO). 1,2 MicroRNA (miRNA), as a short nucleic acid sequence, can control the malignant expression and biological activities of many gene, making it an innovative approach for the preliminary touch and discharge and prognosis recovery of these major diseases. 3−5 Therefore, the excavation of rapid, efficient, and ultrasensitive detection technology of miRNA can not only precipitate the detection rate of diseases effectively but also retrench the window period of pathogen detection greatly.…”
Section: Introductionmentioning
confidence: 99%
“…33 Very recently, Ranjan et al detected the CD44 BC biomarker up to the femto molar concentration using an electrochemical immunosensor based on graphene oxide-ionic liquid-gold nanoparticles (GO-IL-AuNPs). 34 Results suggested that an ILfunctionalized nanocomposite-based immunosensor has an extreme potential to detect bioanalytes at ultralow concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, IL remarkably converts into a more electroconductive nanocomposite when it is incorporated with the nanomaterials. , Shang et al reported an electrochemiluminescence immunosensor of a hybrid nanocomposite of ionic liquid-functionalized graphene-platinum and gold nanoparticles (AuNPs) capped MXene for immunosensing of CEA . Very recently, Ranjan et al detected the CD44 BC biomarker up to the femto molar concentration using an electrochemical immunosensor based on graphene oxide-ionic liquid-gold nanoparticles (GO-IL-AuNPs) . Results suggested that an IL-functionalized nanocomposite-based immunosensor has an extreme potential to detect bioanalytes at ultralow concentrations.…”
Section: Introductionmentioning
confidence: 99%